La imagen variable de la mujer en las crónicas de la exploración y conquista españolas del sureste de norteamérica, 1513-1600 - Moore, Charles B. (2007)
Six Spanish conquerors failed in their attempts to colonize the American southeast in the 16th century. As is the case in other Spanish chronicles of the conquest, women, at first glance, do not figure prominently in the histories of this isolated region, known generically at that time as “Florida.” However, in these close readings of the Spanish chronicles of the southeast, both Spanish as well as Native American women are important players in this forgotten period of Spanish colonial history.